Cytokine profiles in dengue fever and dengue hemorrhagic fever: A study from Indonesia - Masyeni, Sri; Wardhana, I Made W.; Nainu, Firzan (Narra J, 2024)
Recent studies have demonstrated that cytokine dysregulation has a critical role in the pathogenesis of dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). The aim of this study was to investigate the association between tumor necrosis factor (TNF-α), interleukin 6 (IL-6), interleukin 10 (IL-10), and interleukin 17 (IL-17) with infection status, and severity of dengue. A prospective cross-sectional study was conducted at three hospitals in Gianyar regency and Denpasar municipality, Bali, Indonesia, from June to December 2022. Sixty-four dengue infected patients were involved. Patients’ serum was tested for dengue infection using NS1 antigen rapid test, dengue virus immunoglobulin M (IgM) and immunoglobulin G (IgG) test, and reverse transcription polymerase chain reaction (RT-PCR). Cytokine levels (TNF-α, IL-6, IL-10, and IL-17) were measured using enzyme-linked immunosorbent assay (ELISA). Infection status was determined by combining serological and RT-PCR results, categorizing patients into primary and secondary infections. The present study found that DF patients had lower TNF-α, IL-6, and IL-17 but higher IL-10 levels compared to DHF patients (p<0.001). Elevated TNF-α, IL-6, and IL-17 levels were higher in secondary infection, while IL-10 level was higher in primary infection (p<0.001). In conclusion, cytokines play a crucial role in the interplay between cytokine dysregulation and dengue infection dynamics.